2007
DOI: 10.1016/j.brainres.2007.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 5-HT7 receptor mRNA in the hamster brain: Effect of aging and association with calbindin-D28K expression

Abstract: Aging affects several processes modulated by the 5-HT 7 receptor subtype, including circadian rhythms, learning and memory, and depression. Previously, we showed that aging induces a decrease in the hamster dorsal raphe (DRN) in both 5-HT 7 receptor binding and circadian phase resetting responses to 8-OH-DPAT microinjection. To elucidate the mechanisms underlying the aging decrease in 5-HT 7 receptors, we investigated aging modulation of 5-HT 7 receptor mRNA expression in the DRN, brain regions afferent to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 63 publications
(91 reference statements)
4
15
0
Order By: Relevance
“…CB immunoreactivity was abundant throughout the BNST, with an enrichment of cells in medial portions of the BNST in accordance with previous studies in mice (Frantz & Tobin, ). Prominent CB expression has also been noted in the medial BNST of hamsters (Duncan & Franklin, ), rats (Kemppainen & Pitkanen, ; Sequier, Hunziker, Andressen, & Celio, ), primates (Côté, Sadikot, & Parent, ; Fudge & Tucker, ), and humans (Walter, Mai, Lanta, & Görcs, ), suggesting conservation of CB expression in the BNST across multiple species. Approximately 25% of RXFP3+ neurons co‐localized with CB, and 16% of RXFP3+ cells were both GABA+/CB+.…”
Section: Discussionmentioning
confidence: 95%
“…CB immunoreactivity was abundant throughout the BNST, with an enrichment of cells in medial portions of the BNST in accordance with previous studies in mice (Frantz & Tobin, ). Prominent CB expression has also been noted in the medial BNST of hamsters (Duncan & Franklin, ), rats (Kemppainen & Pitkanen, ; Sequier, Hunziker, Andressen, & Celio, ), primates (Côté, Sadikot, & Parent, ; Fudge & Tucker, ), and humans (Walter, Mai, Lanta, & Görcs, ), suggesting conservation of CB expression in the BNST across multiple species. Approximately 25% of RXFP3+ neurons co‐localized with CB, and 16% of RXFP3+ cells were both GABA+/CB+.…”
Section: Discussionmentioning
confidence: 95%
“…The agonist 8-OH-DPAT can act on both the 5HT 1A and 5HT 7 subtype. While age-related changes in response to serotonin agonists have been reported, it is possible that this is not mediated by changes in the 5HT 1A and 5HT 7 receptor subtypes within the SCN, as work has shown that there are no age-related changes in the expression of mRNA for either the 5HT 1A or 5HT 7 receptor with age in the hamster SCN (Duncan et al 1999;Duncan and Franklin 2007). Further work should investigate not only serotonin receptor numbers but also function within the mouse SCN.…”
Section: Discussionmentioning
confidence: 98%
“…The present study extended previous reports of age-related attenuation of SCN expression of VIP mRNA (Krajnak et al, 1998a;Duncan et al, 2001) by demonstrating that aging also decreases SCN expression of mRNA for GRP. It should be noted that aging appears to selectively suppress GRP mRNA and VIP mRNA in the hamster SCN, because no effect of aging has been detected for several other mRNAs expressed in the hamster SCN, including those coding for vasopressin, somatostatin, calbindin-D28 and GAD67 (Duncan & Wheeler, 1999;Duncan et al, 2001;Duncan & Franklin, 2007). Both VIP and GRP are expressed in the ventral SCN (although their distributions are not identical; Moore & Silver, 1998;Morin et al, 2006), which is the region of the SCN that first exhibits changes in expression of the immediate-early gene Fos and circadian clock genes Per1 and Per2, after phase-resetting light pulses (Earnest & Olschowka, 1993;Hamada et al, 2001Hamada et al, , 2004Dardente et al, 2002;Yan & Silver, 2002), and both peptides are involved in mediating light-induced circadian phase shifts.…”
Section: Discussionmentioning
confidence: 99%